DETERMINANTS OF BANK PROFITABILITY IN INDONESIA (CASE STUDY OF INDONESIAN COMMERCIAL BANKS LISTED IN IDX PERIOD 2010-2015) - Watuseke, Christiadi .; Worang, Frederik G.; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract:Banks are the most profitable industries that are able to contribute to the economy. The purpose of this study is to determine the profitability factors of commercial banks in Indonesia by using the industry data panel of banks from 2010 to 2015. This study uses quantitative analysis and secondary financial data using linear regression model for bank size profitability, Asset Return (ROA). The fixed effect regression model is applied for depiction of Bank SIZE, CAR, LDR, NPL, and NIM). The results showed that bank size and NIM have a significant and positive relationship with bank profitability. On the other hand, variables such as NPL and LDR have a negative and significant relationship with bank profitability. However, the relationship to CAR is not significant .Banks in Indonesia should not only be concerned about internal structures and policies, but they must consider both the internal environment and the macroeconomic environment together in fashioning out strategies to improve their performance or profits. Indonesian banks should try their best in order to provide new banking services and to participate in risky investment areas which may in turn increases their profitability significantly.Â Keywords:profitability of bank,nim,ldr,npl,size,car,roaÂ